Evaluation of the prevalence of dietary supplement consumption in selected group of young adults - Kozłowski, Piotr; Kozłowska, Magdalena; Kozłowska, Karolina (Journal of Education, Health and Sport, 2017)
The aim of the study was to evaluate the behavior and habits of dietary supplemnts consumed by adults. The study included 108 participants. In the study group, 67,6% of respondents were females whereas 32,4% were males. The age of participants ranged from 18 to 35 years. The study conducted in the period from January 2017 to March 2017 and it employed standardized interview research method. Research tool, which was used for data collection was a questionnaire consisted of 21 questions single-choice questions. Statistical analysis was performed using the chi-square test. All values for which p <0.05 (probability of error) were considered statistically significant. Respondents were asked about education, knowledge of dietary supplements and frequency of dietary supplements and the reason for their use. More than half of respondents used or currently apply dietary supplements 67.6%. All respondents were convinced of the effectiveness of dietary supplements, especially those of natural origin. Diet supplements were more often used by women (p <0.05), especially with higher education. The reason most women used dietary supplements was the desire to lose weight (31.5% of respondents) and beneficial effects on hair, nails and complexion (29.6% of respondents). Among the group of men, the reason they used to go to dietary supplements was the desire to increase the body’s immunity (38.9% of respondents).Respondents said that they most often use dietary supplements bought at pharmacies (57.4%). As the average time of dietary supplements, the most common response was 2-3 months (50.9%). 7.4% of respondents experienced side effects of dietary supplements (gastrointestinal disorders, headache, rash, skin discoloration).